COVID-19: pharmacology and kinetics of viral clearance (2020)
Coronavirus Disease 2019 (COVID-19) is a pandemic disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The clinical spectrum of COVID-19 is broad and varies from mild to severe forms complicated by acute respiratory distress and death. This heterogeneity might reflect the ability of the host immune system to interact with SARS-CoV2 or the characteristics of the virus itself in terms of loads or persistence. Information on this issue might derive from interventional studies. However, results from high-quality trials are scarce. Here we evaluate the level of evidence of available published interventional studies, with a focus on randomised controlled trials and the efficacy of therapies on clinical outcomes. Moreover, we present data on a large cohort of well-characterized patients hospitalized at a single University Hospital in Milano (Italy), correlating viral clearance with clinical and biochemical features of patients.